Uji Daya Hasil Dua Calon Varietas Jagung (Zea Mays L.) Komposit di Dua Lokasi Di Sumatera Barat - Rika Rahmania; Zulmardi; Marganof (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
The Growth Test of Two Composite Maize (Zea mays L.) Candidate Varieties in Two Locations Payakumbuh City and Agam Regency, West Sumatra" was carried out at Location I in Koto Panjang Village, Lamposi Tigo Nagari District, Payakumbuh City and Location II in Nagari Sungai Batang, Tanjung Raya District, Agam Regency. The objectives of this research are 1. To obtain varieties that are adaptive to the agroecosystem in Payakumbuh City and Agam Regency, 2. To obtain growth tests for two prospective Composite Maize (Zea mays L.) Varieties in Payakumbuh City and Agam Regency. The research was carried out using a Factorial Randomized Block Design (RAK), with each location consisting of 5 treatments and 5 groups, so that there were 25 research plots, each plot consisting of 100 plants, 10 sample plants were taken at random. The treatments were two candidate Composite Corn Varieties Red Jenggel and White Jenggel, three comparison varieties Sukmaraga, Pulut Uri, Yellow Srikandi planted in two locations. Observation parameters, such as plant height, flowering age. The observation data was analyzed for variance using the BNT further test at a significance level of 5%. Research results 1. The two candidates for corn (Zea mays L.) Red Jenggel and White Jenggel are adaptive in the agroecosystem of Payakumbuh City and Agam Regency, 2. Both candidates for Red Jenggel and White Jenggel Composite Corn (Zea mays L.) varieties show better growth in Agam Regency compared to Payakumbuh City when observing plant height